Some technological properties and uses of paulownia (Paulownia tomentosa Steud.) wood - Yıldız, Mehmet Hakan; Şahin Kol, Hamiyet (Journal of Environmental Biology, 31(3): 351-355, 2010)
The aim of this study is to determine some physical and mechanical properties of Paulownia tomentosa wood grown in Turkey. The samples trees harvested from Kargi in Corum. Physical properties including air-dry density, oven-dry density, basic density, swelling, shrinkage and oven-dry and air-dry thermal conductivity coefficients; mechanical properties including bending strength, modulus of elasticity in bending, compression strength parallel to grain, hardness, bonding strength were analyzed. Paulownia tomentosa wood’s air dry and oven dry densities were determined as 0.317 and 0.294 g cm-3; basic density was determined as 0.272 g cm-3; volumetric shrinkage and swelling were determined as 7.78 and 8.41%; tangential, radial and longitudinal air-dry thermal conductivity coefficients were determined as 0.089, 0.090 and 0.133 kcal/mhoC, respectively. Fiber saturation point (FSP) was found 28.79%; bending strength, Modulus of elasticity in bending, compression strength parallel to grain and Brinell hardness values (parallel and perpendicular to grain) were determined as 43.56 N mm-2, 4281.32 N mm-2, 25.55 N mm-2, 2.01 kgf mm-2 and 0.88 kgf mm-2, respectively. Consequently, paulownia wood can be widely used for various purposes such as house construction, furniture making, pulp and paper and handicrafts.
Keywords: Paulownia tomentosa, Technological properties, Thermal conductivity